Novel pathogenic splicing mutation in COL11A1 in a patient with Stickler syndrome verified by minigene splicing assay - Zhang, Jie; Huang, Yaxin; Deng, Yafei; Yang, Xiaochun; Shi, Hong; Yang, Yuecheng; Lv, Tao; Yan, Yuanlong; He, Ming; Liu, Fang (Frontiers in Genetics, 2025)
BackgroundStickler syndrome (STL) is a group of related connective tissue disorders characterized by heterogeneous clinical presentations with varying degrees of orofacial, ocular, skeletal, and auditory abnormalities. However, this condition is difficult to diagnose on the basis of clinical features because of phenotypic variability. Thus, expanding the variant spectrum of this disease will aid in achieving a firm definitive diagnosis of STL.MethodsComprehensive examinations, including ophthalmology, otology, and orthopedic evaluations, were performed to identify the disease phenotype of the proband. Furthermore, whole-exome sequencing (WES) and Sanger sequencing were performed to identify the molecular basis of the disease. In silico analysis and a minigene splicing assay were conducted to verify the pathogenicity of the splice site variant. The clinical phenotypes of the reported STL patients were then reviewed.ResultsThe proband presented mild symptoms with early-onset high myopia and mild scoliosis. A novel de novo splicing variant (NM_080629.3: c.4069-1G>T), in the COL11A1 gene was identified in the proband via WES and confirmed via Sanger sequencing. Minigene splicing assays verified that this variant resulted in abnormal splicing of the COL11A1 transcripts because of the skipping of exon 54 and retention of 21 bp in intron 53. The literature review revealed that the most common phenotypes associated with STL type 2 include myopia and hearing impairment.ConclusionWe identified a novel acceptor splice site variant causing aberrant splicing of COL11A1. Our findings expand the variant spectrum of this gene and provide a precise genetic diagnosis of STL that could be helpful in genetic counseling, reproductive prevention, and treatment of long-term complications of this disorder.